Teknik Penyuntingan Gen Clustered Regularly Interspaced Short Palindromic Repeats-Cas9 (CRISPR-Cas9) sebagai Terapi Penyakit Genetik Bawaan: Ulasan Literatur - Islami, Suryadi; Haq, Rais Amaral; Arianto, Nayla Nadhifa; Sabina, Diana Larisa (CV. Jasa Sukses Abadi, 2024)
The development of therapy for inherited genetic diseases using CRISPR-Cas9 technology has shown significant progress. This article discusses the history and working principles of CRISPR-Cas9, highlighting its applications in the therapy of inherited genetic diseases. Current research focuses include diseases such as cystic fibrosis, thalassemia, and Duchenne muscular dystrophy. Genetic therapy with CRISPR-Cas9 involves editing specific genes to correct disease-causing mutations, opening up opportunities for more effective treatments. Regarding the use of this technique, there are various difficulties, such as potential off-target effects, ethical issues, and long-term safety. However, efforts continue to be made to improve the specificity and accuracy of CRISPR-Cas9 so that the development of effective delivery methods and improving safety has become a major focus of research. Potentially, CRISPR-Cas9 could become a more specific and personalized genetic therapy, opening up opportunities to treat genetic diseases at the molecular level and providing alternative therapies for diseases that were previously difficult to treat. In addition, this technology has the potential for early prevention of genetic diseases and the development of more affordable gene therapies. Interdisciplinary collaboration is key in optimizing the potential of CRISPR-Cas9 to ensure the development of genetic disease therapies that are ethical and beneficial to human health in the future.